2016
DOI: 10.3892/mmr.2016.5852
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cells as a tool for the treatment of glioblastoma multiforme

Abstract: Glioblastoma multiforme is an aggressive malignant brain tumor with terminal consequences. A primary reason for its resistance to treatment is associated with cancer stem cells (CSCs), of which there are currently no effective ways to destroy. It remains unclear what cancer cells become a target of stem cell migration, what the role of this process is in oncogenesis and what stem cell lines should be used in developing antitumor technologies. Using modern post-genome technologies, the present study investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 35 publications
0
19
0
1
Order By: Relevance
“…Resident microglia are described to be involved in many processes including tumor growth and progression (Bryukhovetskiy et al, 2016;Matias et al, 2018). Microglia were shown to contribute to the invasiveness of GB by upregulating serpin family A member 3 (SERPINA3) expression in GB stem cells (GSCs), that is implicated in the remodeling of the extracellular matrix .…”
Section: Microglia: the Resident Macrophages Of The Cnsmentioning
confidence: 99%
“…Resident microglia are described to be involved in many processes including tumor growth and progression (Bryukhovetskiy et al, 2016;Matias et al, 2018). Microglia were shown to contribute to the invasiveness of GB by upregulating serpin family A member 3 (SERPINA3) expression in GB stem cells (GSCs), that is implicated in the remodeling of the extracellular matrix .…”
Section: Microglia: the Resident Macrophages Of The Cnsmentioning
confidence: 99%
“…Median survival time of GBM patients is approximately 12–15 months after the first diagnosis ( 2 ). Conventional treatments for GBM patients are mostly surgical tumor excision followed by chemotherapy or radiation therapy ( 3 ). Although the therapies have increased the survival time to approximately 14.6 months, the advantages are unconspicuous ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Normal CD45 + CD34 + HSCs are able to migrate to cells of different types, although they have increased mobility towards cancer cells. In animals with implanted glial brain tumors, intravenously injected HSCs migrate to the tumor nidus and accumulate in areas of invasion and necrosis ( 32 ). A previous study reported that hematopoietic CD34 + CD45 + stem cells migrate towards glioblastoma cells and interact with them, indicative of a strong association between these cell types ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…In animals with implanted glial brain tumors, intravenously injected HSCs migrate to the tumor nidus and accumulate in areas of invasion and necrosis ( 32 ). A previous study reported that hematopoietic CD34 + CD45 + stem cells migrate towards glioblastoma cells and interact with them, indicative of a strong association between these cell types ( 32 ). It is possible that by recruiting bone marrow cells, the tumor creates its own microenvironment, allowing it to optimize resources and escape the innate immune system and other defense mechanisms of the body ( 32 ).…”
Section: Discussionmentioning
confidence: 99%